Seroprevalence of Brucellosis in goats in some selected areas of Bangladesh - Munsi, Md Nuruzzaman; Akther, Sonia; Rahman, Md Habibur; Hassan, Md Zakir; Ali, Md Zulfekar; Ershaduzzaman, Md (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study aimed to explore the seroprevalence of Brucella spp. in goats in some selected areas of Bangladesh. Materials and Methods: This study was conducted in different goat-populated regions of Bangladesh from July 2017 to June 2018. A total of 208 serum samples were randomly collected from goats in Jashore (n = 50), Jhenidah (n = 22), Tangail (n = 40), Savar (n = 46), Thakurgaon (n = 18), and Bandarban (n = 32) areas. The samples were subjected to determine the presence of antibodies against Brucella spp. by rose bengal plate test (RBPT) and competitive enzyme-linked immunosorbent assay (c-ELISA). Results: Overall, the seroprevalence of Brucellosis in goats was 4.33% (n = 9/208) by RBPT and 2.40% (n = 5/208) by c-ELISA. The seroprevalence of brucellosis on the basis of RBPT was 6% (buck: 0%, doe: 6%) in Jashore, 4.5% (buck: 0%, doe: 4.5%) in Jhenidah, 2.5% (buck: 0%, doe: 2.5%) in Tangail, 4.35% (buck: 0%, doe: 4.35%) in Savar, 6.25% (buck: 0%, doe: 6.25%) in Bandarban, and 5.56% (buck: 0%, doe: 5.56%) in Thakurgaon. On the other hand, the seroprevalence of brucellosis by c-ELISA was 4% (buck: 0%, doe: 4%) in Jashore, 4.5% (buck: 0%, doe: 4.5%) in Jhenidah, 3.13% (buck: 0%, doe: 3.13%) in Bandarban, and 5.56% (buck: 0%, doe: 5.56%) in Thakurgaon. Brucellosis was more prevalent (p > 0.001) in does aging 3–4 years. Conclusion: Goats from different areas of Bangladesh are caring antibodies against Brucella organisms. Further bacteriological investigations are necessary. J. Adv. Vet. Anim. Res., 8(1): 123-128, Mar 2021 http://doi.org/10.5455/javar.2021.h494